Fires, Smoke Exposure, and Public Health: An Integrative Framework to Maximize Health Benefits From Peatland Restoration. Issue 7 (24th July 2019) - Marlier, Miriam E.; Liu, Tianjia; Yu, Karen; Buonocore, Jonathan J.; Koplitz, Shannon N.; DeFries, Ruth S.; Mickley, Loretta J.; Jacob, Daniel J.; Schwartz, Joel; Wardhana, Budi S.; Myers, Samuel S.
Abstract: Emissions of particulate matter from fires associated with land management practices in Indonesia contribute to regional air pollution and mortality. We assess the public health benefits in Indonesia, Malaysia, and Singapore from policies to reduce fires by integrating information on fire emissions, atmospheric transport patterns, and population exposure to fine particulate matter (PM2.5 ). We use adjoint sensitivities to relate fire emissions to PM2.5 for a range of meteorological conditions and find that a Business‐As‐Usual scenario of land use change leads, on average, to 36, 000 excess deaths per year into the foreseeable future (the next several decades) across the region. These deaths are largely preventable with fire reduction strategies, such as blocking fires in peatlands, industrial concessions, or protected areas, which reduce the health burden by 66, 45, and 14%, respectively. The effectiveness of these different strategies in mitigating human health impacts depends on the location of fires relative to the population distribution. For example, protecting peatlands through eliminating all fires on such lands would prevent on average 24, 000 excess deaths per year into the foreseeable future across the region because, in addition to storing large amounts of fuel, many peatlands are located directly upwind of densely populated areas. We also demonstrate how this framework can be used to prioritize restoration locations for the Indonesian Peatland Restoration Agency based on their ability to reduce pollution exposure and health burden. This scientific framework is publicly available through an online decision support tool that allows stakeholders to readily determine the public health benefits of different land management strategies. Plain Language Summary: Regularly occurring fires in Indonesia are associated with drought conditions and agricultural practices. These fires contribute to dangerous levels of particulate matter pollution that are harmful to public health throughout the region. We develop an interdisciplinary scientific framework to connect land use decisions with fire activity and public health outcomes. Our estimates find that if current trends continue, exposure to air pollution from Indonesian fires would cause, on average, 36, 000 excess deaths per year across Indonesia, Malaysia, and Singapore. These deaths can be prevented through land management strategies, which would reduce the number of deaths attributable to air pollution from fires. Current plans to restore peatlands would reduce regional fire emissions‐related mortality by approximately 66% if fully implemented. Key Points: Current trends in Indonesia's fire activity would lead to 37, 000 excess deaths per year across the region from air pollution exposure Restoring peatlands could reduce fire‐related mortality by nearly 70% Our integrative scientific tool can be used to support land management strategies most beneficial for public health